Aktivitas Cyber Public Relations Pada Agen Perjalanan Online Dalam Meningkatkan Brand Awareness - Anindita Susilo (Jurnal Spektrum Komunikasi, 2020)
In the globalization era, technological development plays a huge impact on various aspects, for example, the development of online travel agents in Indonesia. One of the most widely used online travel agents in Indonesia is Pegipegi.com. This is proven from the results of the DailySocial.id survey, which states that Pegipegi.com ranks third for airplane ticket purchases (27.47%) and trains (24.06%), and fifth for hotel bookings (19.47%). In early 2018, Pegipegi.com also managed to get two awards, namely as Silver Champion in the Indonesia WOW Brand 2018 event and Netizen Online Reservation Choice in the Indonesia Netizen Brand Choice Award 2018. This study aims to determine the implementation of cyber PR in online travel agents (Pegipegi.com) in increasing brand awareness so that it can be input for other online travel agents. The method used in this research is descriptive qualitative. Data were collected through interviews. The results showed that Digital Public Relations activities carried out by Pegipegi.com to increase brand awareness is by collaborating with online media in the form of advertorial writing and utilizing media assets owned in the form of social media and blogs specifically for the world of travel. One of the activities that are quite interesting to the public is the writing competition on social media (writing competition) and collaborating with YouTube accounts and social media from the Key Opinion Leaders (KOL).